Epigenetic screening of salivary gland mucoepidermoid carcinoma identifies hypomethylation of CLIC3 as a common alteration. Issue 12 (December 2015) - Wang, Zhiming; Ling, Shizhang; Rettig, Eleni; Sobel, Ryan; Tan, Marietta; Fertig, Elana J.; Considine, Michael; El-Naggar, Adel K.; Brait, Mariana; Fakhry, Carole; Ha, Patrick K.
Highlights: The HumanMethylation27 BeadChip array was used in a cohort of mucoepidermoid carcinoma. The increased protein expression of CLIC3 via IHC was noted in MEC versus normal salivary gland tissues. CLIC3 was found to have significant hypomethylation in these MEC tumors. Summary: Objectives: The role of promoter methylation in the development of mucoepidermoid carcinoma (MEC) has not been fully explored. In this study, we investigated the epigenetic landscape of MEC. Methods: The Illumina HumanMethylation27 BeadChip array and differential methylation analysis were utilized to screen for epigenetic alterations in 14 primary MEC tumors and 14 matched normal samples. Bisulfite sequencing was used to validate these results, with subsequent quantitative Methylation-Specific PCR (qMSP) to validate chloride intracellular channel protein 3 (CLIC3) in a separate cohort. Furthermore, CLIC3 immunohistochemical (IHC) staining was performed in another separate cohort of MEC. Finally, clinical and pathological characteristics were statistically analyzed for correlation with methylation status of CLIC3 and CLIC3 IHC H-scores by Wilcoxon rank sum, Kruskall–Wallis, and X 2 test tests. Results: We obtained 6 significantly differentially methylated gene candidates demonstrating significant promoter hyper- or hypo-methylation from the array data. Using bisulfite sequencing, we found one gene, CLIC3, which showed differential methylation between MEC tumor and normal samples in a small validation cohort. qMSP analysis of the CLIC3 promoter in a separate validation set showed significantly lower methylation level in tumor than in normal. The level of CLIC3 methylation in MECs was not statistically correlated with clinical or pathological characteristics. However, IHC staining intensity and distribution of CLIC3 were significantly increased in MECs, compared with those of normal salivary gland tissues. Conclusions: Hypomethylation of CLIC3 promoter and its overexpression are significant events in MEC. Its functional role and potential therapeutic utility in MEC are worthy of further exploration.